Development of a Solar Distilling Roofing System for Drinking Water Supply - Sa’adan, Nurulain (IRC, 2016)
Lack of clean water in small remote communities in the developing world is a major health problem. Water purification and desalination systems powered by solar energy such as passive solar distillation system are potential solutions to the clean water problems in these small communities. This work investigates the quality of water purified by solar light using roof distillation system to treat the groundwater. Passive solar system has been proposed in previous research by using slanted single or double glass over with the help of solar panel.